Usefulness of Double-Balloon Endoscopy in the Postoperative Gastrointestinal Tract - Masaki Endo; Yukito Abiko; Syuhei Oana; Norihiko Kudara; Takashi Kosaka; Toshimi Chiba; Yasuhiro Takikawa; Kazuyuki Suzuki; Tamotsu Sugai (Gastroenterology Research and Practice)
Background. The small intestine has been considered to be a highly difficult organ to visualize in imaging examinations due to its anatomical location compared with the stomach and the colon. In recent years, many imaging modalities have become available, such as CT enterography, MR enterography, capsule endoscopy (CE), and double-balloon endoscopy (DBE). Patients and Methods. DBE was performed in the postoperative intestines of 91 patients (128 DBE examinations) at Iwate Medical University between 2004 and 2010. There were 61 male and 30 female patients, and their mean age was 69.7 years (range: 30–80 years). Results. A total of 124 DBE examinations were performed with endoscope insertion into the reconstructed intestines. The endoscope reached the blind end in 115 of 124 examinations, (92.7%). There were 17 patients with obscure gastrointestinal bleeding in whom 30 DBE examinations were performed. The bleeding site was identified in 12 patients (70.6%). Nine patients underwent endoscopic treatment. Hemostasis was achieved in all patients. Conclusion. DBE is very useful modality for the assessment and application of endotherapy to areas of the small bowel which have been altered by surgery.